Guadalupe, Honduras. Kulturelle Interaktion und vorspanische Siedlungsgeschichte im Nordosten von Honduras. Die Arbeiten des Jahres 2018 - Reindel, Markus; Fux, Peter; Fecher, Franziska (e-Forschungsberichte des DAI, 2019)
In spring 2018, the third field campaign of the archaeological project Guadalupe took place. Since 2016 the project has been undertaking excavations, topographic measurements and surveys in and near the Cocal period (AD 1000–1521) archaeological site of Guadalupe located on the northeastern Atlantic coast of Honduras. The aim of the project is to contribute to the investigation of the cultural processes in this little studied region at the frontier between Mesoamerica and the Istmo-Columbian Area.